Features of trunk muscle wasting during acute care and physical function recovery with aortic disease. Issue 2 (17th February 2022) - Yamashita, Masashi; Kamiya, Kentaro; Matsunaga, Atsuhiko; Kitamura, Tadashi; Hamazaki, Nobuaki; Ichikawa, Takafumi; Uchida, Shota; Noda, Takumi; Yanagi, Naoya; Maekawa, Emi; Yamaoka‐Tojo, Minako; Ako, Junya; et al.
Abstract: Background: Low skeletal muscle area or density, such as myosteatosis, identified on computed tomography (CT) is associated with poor prognosis in patients with cardiovascular diseases. However, there is a lack of evidence regarding the clinical process of skeletal muscle decline as a short‐term change during acute care settings. This study focused on the use of routine CT imaging for aortic disease management and investigated the changes in skeletal muscle before and after acute care. Methods: This prospective study included 123 patients who underwent abdominal CT before and after acute care. The all‐abdominal and each abdominal muscle areas were divided into eight parts (e.g. rectus abdominis, psoas, and erector spine), and their areas and densities were measured at the third lumbar vertebra level after the patients were discharged and de‐identified with blinding to avoid measurement bias. Short physical performance battery (SPPB) was measured at the start and end of in‐hospital cardiac rehabilitation. A generalized linear model with patients as random effects was made to investigate skeletal muscle loss during acute care. Multivariate linear regression analysis was also used to assess the relationship between the change in skeletal muscle during acute care and SPPB during in‐hospital cardiac rehabilitation. Results: The median age of the patients was 70 (interquartile: 58–77) years, and 69.9% (86/123) were men. The median day between acute care from the day of surgery or hospital admission and follow‐up CT was 7 (interquartile: 3–8) days. Overall muscle density declined after acute care (estimate value: −3.640, 95% confidence interval [CI]: −4.538 to −2.741), and each abdominal muscle density consistently declined (interaction: F value = 0.099, P  = 0.998). In contrast, there was no significant change in the overall muscle area (estimate value: −0.863, 95% CI: −2.925 to 1.200). Changes in the muscle area were different for each skeletal muscle (interaction: F value = 2.142, P  = 0.037), and only the erector spine muscle significantly declined (estimate value: −1.836, 95% CI: −2.507 to −1.165). After adjusting for confounding factors, a greater decline in muscle density was associated with lower recovery score on SPPB (β = 0.296, 95% CI: 0.066 to 0.400). Conclusions: Muscle density consistently declined after acute care, especially the erector spine muscles, which also significantly decreased in size. A higher decline in muscle density was associated with a slower recovery of physical function during in‐hospital cardiac rehabilitation in patients with aortic diseases.